Characterization Of Denture Base Poly (Methyl Methacrylate) Reinforced With Alumina/Zirconia Particles - alHareb, Ahmed Omran Salem (2011)
The properties of PMMA matrix composite incorporated with alumina (Al2O3) and yttria-stabilized zirconia poly crystal (Y-TZP) powders, as dental base material, was studied. The limitation of PMMA matrix is due to its weak fracture toughness. The PMMA powder was mixed with liquid MMA monomer and stabilized with 0.0025% hydroquinone. Benzoyl peroxide (BPO) and ethylene glycol dimethacrylate (EGDMA) were used as initiator and as cross-linking agent, respectively. The study was divided into two different stages.